A direct gateway into the extracellular space: unconventional secretion of FGF2 through self-sustained plasma membrane pores - Steringer, Julia P.; Nickel, Walter (Seminars in cell & developmental biology, 2018)
As illustrated by a diverse set of examples in this special issue, multiple mechanisms of protein secretion have been identified in eukaryotes that do not involve the endoplasmic reticulum (ER) and the Golgi apparatus. Here we focus on the type I pathway with Fibroblast Growth Factor 2 (FGF2) being the most prominent example. Unconventional secretion of FGF2 from cells is mediated by direct protein translocation across the plasma membrane. A unique feature of this process is the ability of FGF2 to form its own membrane translocation intermediate through oligomerization and membrane insertion. This process depends on the phosphoinositide PI(4,5)P2 at the inner leaflet and results in the formation of lipidic membrane pores in the plasma membrane. Various lines of evidence suggest that these pores are characterized by a toroidal architecture with FGF2 oligomers being accommodated in the center of these structures. At the outer leaflet of the plasma membrane, membrane proximal heparan sulfate proteoglycans are required for the final step of FGF2 translocation into the extracellular space. Based upon mutually exclusive interactions of FGF2 with PI(4,5)P2 versus heparan sulfates, an assembly/disassembly pathway has been proposed to be the underlying principle of directional transport of FGF2 across the plasma membrane. Thus, the core mechanism of unconventional secretion of FGF2 is based upon three discrete steps with (i) PI(4,5)P2 dependent oligomerization of FGF2 at the inner leaflet, (ii) insertion of membrane spanning FGF2 oligomers into the plasma membrane and (iii) disassembly at the outer leaflet mediated by heparan sulfates that subsequently retain FGF2 on cell surfaces. This process has recently been reconstituted with an inside-out membrane model system using giant unilamellar vesicles providing a compelling explanation of how FGF2 reaches the extracellular space in an ER/Golgi independent manner. This review is part of a Special Issue of SCDB on “unconventional protein secretion” edited by Walter Nickel and Catherine Rabouille.
Gesehen am 15.04.2020